Congenital bilateral perisylvian syndrome - Yildirim, Hanefi; Koc, Mustafa; Poyraz, Kuersad; Ogur, Erkin; Kabakus, Nimet (Ortadogu Ad Pres & Publ Co, 2008)
Congenital bilateral perisylvian syndrome is a structural malformation of the brain which normal pattern of folds on the surface of the brain is replaced with many small abnormal folds. The underlying anomaly is polymicrogyria, a malformation of the cerebral cortex. Polymicrogyria refers to excessive number of prominent and small convolutions composed from shallow and enlarged sulci. This anomaly constitutes lobular appearance of cerebral cortex. We present cranial magnetic resonance imaging (MRI) findings of a 3-year old male patient who was admitted with asymmetric facial paralysis, chewing and swallowing difficulties and intractable seizures. Brain MRI revealed bilateral perisylvian cortical dysplasia including polymicrogyria and local cortical thickening that extends to the level of vertex.
Keywords: congenital; brain; epilepsy; rolandic; magnetic resonance imaging